Tasmim Ahdaf Ta'lim al-Muthala'ah al-Mu'tamadah 'Ala Tahlili al-Hajah Fi Syu'bah Ta'lim al-Lughah al-Arabiyah Bi Jami'ah Curup al-Islamiyah al-Hukumiyah - Rini Rini (Arabiyatuna: Jurnal Bahasa Arab, 2018)
Students who choose to continue their studies in the IAIN Arabic education study program Curup face difficulties in learning Arabic. One of the difficulties faced is the difficulty in understanding Arabic reading, the feeling of being bored and the lack of a communicative atmosphere in learning. This in turn results in their ability to read Arabic. one of the solutions that must be done by the IAIN Curup Arabic education study program to overcome the above problems is by evaluating and improving the muthala'ah curriculum, in which one of the elements of the curriculum is the learning goal. The method used in this study is qualitative. In accordance with the problems studied, this study uses a case study. Choose a case study design because the study focuses on one program, namely reading comprehension. The results of this study are that the muthala'ah learning objectives in the Arabic IAIN Curup education study program include literal reading, interpretive reading, critical reading and creative reading consisting of competency standards and basic competencies.